1991
DOI: 10.1029/90ja02572
|View full text |Cite
|
Sign up to set email alerts
|

Explosive events and magnetic reconnection in the solar atmosphere

Abstract: Explosive events are highly energetic, small‐scale phenomena which are frequently detected throughout the quiet and active Sun. They are seen in profiles of spectral lines formed at transition zone temperatures as exceptionally Doppler‐shifted features, typically at 100 km s−1 to the red and/or blue of the rest wavelength. Sufficient observational evidence has now been developed to demonstrate that some explosive events are associated with the emergence of new magnetic flux. In these cases it is likely that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
88
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(94 citation statements)
references
References 27 publications
5
88
1
Order By: Relevance
“…They are not associated with X-ray bright points (Moses et al 1994). Cancellations of photospheric magnetic fields observed in relation to explosive events (Dere et al 1991;Chae et al 1998c) and bidirectional jets (Innes et al 1997a) or chromospheric upflow events (Chae et al 1998d) are strong indications of a generation process by reconnection. The spectroscopic signature of bidirectional jets seems to be a characteristic feature of explosive events.…”
Section: Explosive Eventsmentioning
confidence: 93%
See 1 more Smart Citation
“…They are not associated with X-ray bright points (Moses et al 1994). Cancellations of photospheric magnetic fields observed in relation to explosive events (Dere et al 1991;Chae et al 1998c) and bidirectional jets (Innes et al 1997a) or chromospheric upflow events (Chae et al 1998d) are strong indications of a generation process by reconnection. The spectroscopic signature of bidirectional jets seems to be a characteristic feature of explosive events.…”
Section: Explosive Eventsmentioning
confidence: 93%
“…The first density results of n e ≈ 7 × 10 10 cm −3 were obtained by Dere et al (1991). Line-ratio studies later indicated that there is a density increase by a factor of about three and, in some cases, a significant electron temperature increase (Wilhelm et al 1998c;Teriaca et al 2001Teriaca et al , 2002aMendoza-Torres et al 2005).…”
Section: Explosive Eventsmentioning
confidence: 99%
“…De Pontieu et al 2007;Hasan & van Ballegooijen 2008;van Ballegooijen et al 2011;Meyer et al 2013;De Pontieu et al 2014) but at present there is no clear consensus about which dominates. Above the chromosphere, the slightly hotter transition region network is characterised by small, highly dynamic brightenings and jets Aiouaz 2008) that are thought to result from magnetic reconnection (Dere et al 1991;Innes et al 1997b). At higher temperatures, the network mixes with diffuse coronal emission and loops (Feldman et al 2000) in which sudden small-scale X-ray brightenings are seen at a rate of about one every three seconds for the whole Sun (Krucker et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Dere et al (1991) suggested that they are produced by bi-directional jets as a result of magnetic reconnection. To date, these jetlike events (often called explosive events) are mainly observed in spectral lines formed at transition region temperatures (Dere 1994;Chae et al 1998;Innes et al 2001;Madjarska & Doyle 2003), although observations of explosive events in chromospheric lines are also reported.…”
Section: Introductionmentioning
confidence: 99%